PENGARUH PERUBAHAN KEWAJIBAN IMBALAN KERJA, STRUKTUR MODAL DAN RETURN ON EQUITY TERHADAP EARNINGS RESPONSE COEFFICIENT SEBAGAI DAMPAK DARI PENGADOPSIAN PSAK 24 REVISI 2013 (Studi Empiris Pada Perusahaan Manufaktur Tahun 2013-2015) - B2091151014, TEDDY ORLANDO (FAKULTAS EKONOMI DAN BISNIS UNTAN, 2017)
This research aimed to find out empirical evidence about the influence of employee benefits liabilities, capital structure and return on equity to earnings response coefficient in its relation to adoption of PSAK 24 revision 2013 to the company which is listed as manufacturing company for 2013-2015. Earnings Response Coefficient which measured by regression from change in earnings per share with cummulative abnormal return as the dependent variable, while chajnge employee benefits liabilities, capital structure and return on equity as the independent variables. Purposive sampling method is used in this research to determine the samples, with total 44 samples.Multiple linear regression analysis shows that change in employee benefits liabilities, capital structure and return on equity do not have significant influence to earnings response coefficient.Â Keywords: Employee benefits liabilities, Capital Structure, Return On Equity, Earnings Response Coefficient.